Implementation of Open High School Program at Dflomnhs - Balbin, Catherine C.; Sumail, Ederlina M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study assessed the implementation and challenges of the Open High School Program (OHSP) at Doña Francisca Lacsamana de Ortega Memorial National High School (DFLOMNHS), an alternative educational model designed for learners unable to attend traditional classes due to personal, economic, or geographic barriers. Using a mixed-methods descriptive-correlational design, the study surveyed 48 learners and 16 teacher-implementers through validated questionnaires, with reliability coefficients ranging from 0.931 to 0.986. Quantitative data were analyzed using means, t-tests, and Pearson correlations, while qualitative responses were subjected to thematic analysis. Findings revealed that most learners were female (70.83%), aged 16–20, from low-income households (81.25%), and had parents with low educational attainment. While 35.42% of learners performed at an outstanding academic level, 20.84% did not meet expectations. The OHSP was generally well-implemented across four dimensions (M = 3.37 for learners, M = 3.32 for teachers), with no statistically significant difference in perceptions (t = 0.24, p = 0.82). Correlational analysis showed no significant relationships between implementation and learner or teacher profiles, underscoring the program’s equitable reach. However, recurring challenges included limited parental support, inconsistent technology access, and gaps in teacher coordination and instructional delivery. Aligned with global findings on flexible education and student engagement, this study highlights the potential of OHSP to promote educational equity. It recommends enhanced parent training, regular teacher upskilling in digital pedagogy, and stronger community-school collaboration to sustain and improve program outcomes.